Buscando a Alaska - Green, John, 1977- (Ediciones Castillo, 2006)
Sixteen-year-old Miles' first year at Culver Creek Preparatory School in Alabama includes good friends and great pranks, but is defined by the search for answers about life and death after a fatal car crash.